MALIGNANT PERIPHERAL NERVE SHEATH TUMOR– BIOLOGICALLY AGGRESSIVE SOFT TISSUE SARCOMAS: CASE REPORT - Hadzi - Manchev, Todor; Ognjenovikj, Ljubomir; Karadzov, Zoran; Gjosev, Stojan; Hadzi-Manchev, Dragan; Dzambaz, Darko; Shumenkovski, Velimir (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
Primary retroperitoneal tumors are an exceedingly rare clinical problem. Masses in the retroperitoneum can be categorized as one of three entities: lymphomas, extragonadal germ cell tumors, and sarcomas. Malignant peripheral nerve sheath tumors are uncommon, biologically aggressive soft tissue sarcomas of neural origin that pose tremendous challenges to effective therapy. We present a young adult with retroperitoneal tumor. The patient presented a lumbar pain on the left side. Echotomography of the abdomen was madeand cystic tumor under the pancreas was detected. CT showed retroperitoneal tumor with hypodense features,with defined borders with size of 5,6x9,6 cm. Blood results and tumor markers showed no abnormalities. The patient had a surgery and  whole extirpation was made without damaging the surrounding organs.This case illustrate early diagnosis of MPNST is key to reduce mortality, with complete surgical extirpation with clear margins as treatment of choice. Key words: Retroperitoneal tumor, soft tissue sarcomas, surgical extirpation https://doi.org/10.55302/JMS2141101hm